Moderating Role of Quiet Ego in the Relationship Between Psychological Well-Being and State Anxiety in Adolescents - Aliyev, R; Demirdag, B (My University)
Adolescence is a key period for psychological well-being, during which state anxiety poses a significant risk. Emphasizing the development of self-resources is crucial in mitigating such risks. The quiet ego, as a positive self-resource, supports psychological well-being; however, its role in relation to state anxiety has been insufficiently explored in the literature. The current study contributes to literature examining the quiet ego during adolescence and explaining its role in the relationship between psychological well-being and state anxiety. This study was conducted to examine the relationship between adolescents' psychological well-being, state anxiety and the quiet ego levels. The sample of the study carried out in the correlational research model consisted of 1178 adolescents attending 9th-12th grades. The research group was selected through simple random sampling. Data were analyzed using t-test, one-way analysis of variance (ANOVA), and Hayes' PROCESS macro Model 1. Findings indicate that adolescents' psychological well-being, state anxiety and the quiet ego levels differ significantly based on gender, accessibility of guidance services, number of friends, interest in arts and sports and perceived parental attitudes. State anxiety was moderately negatively associated with psychological well-being, while the quiet ego showed a moderate positive relationship with psychological well-being and a weak negative relationship with state anxiety. Moderating role analysis pointed out that the moderating role of the quiet ego in the relationship between psychological well-being and state anxiety was not significant. The ongoing development of the self during adolescence may have influenced the non-significant moderating effect of the quiet ego. Nonetheless, its associations with psychological well-being and state anxiety suggest that it serves as an alternative self-resource supporting psychological well-being. These findings show that it is important to develop programs that support the development of the quiet ego in preventive mental health practices for adolescents.
Keywords: Psychological well-being; state anxiety; quiet ego